PENDAMPINGAN PENGENALAN HUBUNGAN INDONESIA-INDIA TENTANG BUDAYA INDIA DI INDONESIA - Riza Afita Surya (LPPM Universitas Bina Bangsa, 2022)
Community service in the form public lectures target students of the history education program, University of Jember. The problems faced by students and need to be solved through this community service program include, (1) lack understanding of Indian culture in Indonesia, (2) lack understanding of students about the implications of Indian culture in Indonesia and (3) there has never been a public lecture on culture. India in Indonesia before. The solutions to be achieved include; (1) giving public lectures on Indian culture in Indonesia by Indian experts and classical historians, (2) providing direction to students on approaches to learning about Indian culture in Indonesia, and (3) establishing academic cooperative relationships with Indian academics.